2015
DOI: 10.1038/mp.2015.176
|View full text |Cite
|
Sign up to set email alerts
|

Activation of a ventral hippocampus–medial prefrontal cortex pathway is both necessary and sufficient for an antidepressant response to ketamine

Abstract: A single sub-anesthetic dose of ketamine exerts rapid and sustained antidepressant effects. Here, we examined the role of the ventral hippocampus (vHipp)-medial prefrontal cortex (mPFC) pathway in ketamine's antidepressant response. Inactivation of the vHipp with lidocaine prevented the sustained, but not acute, antidepressant-like effect of ketamine as measured by the forced swim test (FST). Moreover, optogenetic as well as pharmacogenetic specific activation of the vHipp-mPFC pathway using DREADDs (designer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
160
4
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(171 citation statements)
references
References 44 publications
6
160
4
1
Order By: Relevance
“…[9][10][11][12][13]90 A possible change in AMPAR and NMDAR functions in mediating the antidepressant effect of ketamine is supported by a study using magnetic resonance spectroscopy in healthy human controls showing an increased glutamine/glutamate ratio induced by ketamine after 24 h, reflecting increased synaptic glutamate neurotransmission, specifically in frontal cortical regions with high density of AMPARs. 91 Our present data, which demonstrate a reduced synaptic potentiation and AMPAR function in VTA-NAc circuit, may therefore appear contradictory.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…[9][10][11][12][13]90 A possible change in AMPAR and NMDAR functions in mediating the antidepressant effect of ketamine is supported by a study using magnetic resonance spectroscopy in healthy human controls showing an increased glutamine/glutamate ratio induced by ketamine after 24 h, reflecting increased synaptic glutamate neurotransmission, specifically in frontal cortical regions with high density of AMPARs. 91 Our present data, which demonstrate a reduced synaptic potentiation and AMPAR function in VTA-NAc circuit, may therefore appear contradictory.…”
Section: Discussionmentioning
confidence: 75%
“…Several lines of evidence suggest that depression is associated with altered synaptic plasticity of excitatory synapses and that ketamine promotes AMPAR function and synaptogenesis. [9][10][11][12][13] Thus, modulation of glutamatergic neurotransmission and plasticity in the hippocampus and medial prefrontal cortex is suggested to mediate the antidepressant action of ketamine. [9][10][11][12][13] Both AMPARs and NMDARs are critical elements of forms of long-term synaptic plasticity such as longterm potentiation (LTP), a potential neurophysiological correlate of learning and memory.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, other optogenetic approaches revealed that a selective population of neurons in medial prefrontal cortex (PFC) is implicated in the active response to behavioral challenges (Warden et al, 2012). More recently, optogenetic approaches have also shown that activation of the ventral-hippocampus-medial PFC pathway is required for the sustained action of ketamine antidepressant action, observed as an increase in climbing in the FST (Carreno et al, 2016). Although a similar mechanism probably operates in our stress model, the suggested Fasudil antidepressant action in the FST must be interpreted with caution, and further studies are required to prove its action on specific circuits that are sensitive to stress, such as those related to motivated behavior.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, work in cultured cortical and hippocampal murine neurons showed that ketamine selectively potentiated extrasynaptic GABA A R–mediated tonic inhibition (136), a function fulfilled largely by α5-GABA A Rs, hence providing a putative mechanism reconciling acute SST cell blockade by rapid-acting antidepressants, with prolonged cellular effects ultimately leading to increased SST cell function. Notably, rapid-acting antidepressant mechanisms may also depend on subcortical structures, as ventral hippocampus inactivation prevented sustained antidepressant-like effects of ketamine in rats (137). …”
Section: Target Engagement and Therapeutic Approachmentioning
confidence: 99%